Question
Sat July 09, 2011 By: Prashanth Vasudevan

Find x & y.

Expert Reply
Sun July 10, 2011

The given equations are:

2(ax-by)+a+4b=0             ... (1)

2(bx+ay)+b-4a=0             ... (2)

Multiplying (1) by a and (2) by b,

2a2x - 2aby + a2 + 4ab = 0

2b2x + 2aby + b2 - 4ab = 0

Adding the above two equations,

2(a2 + b2)x + a2 + b2 = 0

2(a2 + b2)x = -(a2 + b2)

x = -1/2

Putting this value of x in (1), we get

2ax - 2by + a + 4b=0

-a - 2by + a + 4b=0

- 2by + 4b=0

2by = 4b

y = 2

Ask the Expert